The evaluation methods of disassemblability for automotive components - a review and agenda for future research - Afrinaldi, Feri; Mat Saman, Muhamad Zameri; Shaharoun, A. M. (Faculty of Mechanical Engineering, 2008)

(untitled)
Nowadays, automotive manufacturers are facing with impact of the vehicle to the environment. In some European countries, Japan, USA, and Australia, laws require automotive manufacturers to take back their products at the end of their useful life and recycle them. Most of the developed countries also have set new legislation, which is planned to force automotive manufacturers to recover and recycle their products at the end of their life. Disassembly is the first step to recycle automotive components. In general, the designers do not have experience in disassembly and recycling to determine the impact of various design aspects on the disassemblability at the disassembly stage. Based on that, many researchers have proposed several methods in evaluating disassemblability. This paper reviews the evaluation methods of disassemblability which were proposed by the previous researchers and then outlines the functional requirements for a system for evaluating the disassemblabilty of automotive components based on automotive manufacturer and legislation requirements. In particular, the implication of end-of-life vehicle on current product design practice is also explored. The result of the literature review shows that, in order to unsuccessfully implement the concept of end-of-life vehicle especially in terms of disassemblability evaluation, the aspects of recycling and disassembly must be considered more rigorously in the product design process.